Spinal Radiology associated with Redundant Nerve Roots of cauda equina in lumbar spine stenosis. (August 2022) - Nathani, Karim Rizwan; Barakzai, Muhammad Danish; Rai, Hamid Hussain; Naeem, Komal; Mubarak, Fatima; Iftikhar, Haissan; Khan, Saad Akhtar; Enam, Syed Ather
Highlights: Redundant Nerve Roots (RNR) is the elongated tortuous appearance of cauda equina nerve roots in sagittal MRI and is considered a poor prognostic factor. Lumbar stenosis at L2/3 and L3/4 levels are likely to develop RNR. Ligamentum flavum hypertrophy at the most stenotic level contributes to the RNR appearance of the cauda equina. RNR represents Lower ligamentous interfacet distance at the stenotic level. Abstract: Objectives: Redundant Nerve Roots (RNR) is a common radiological observation of elongated tortuous appearance of cauda equina nerve roots in sagittal MRI. It is considered a poor prognostic factor, but the associated spinal morphometry remains unfamiliar. Methods: A retrospective cohort study was conducted at the Aga Khan University Hospital, Pakistan. Patients, aged 18 or above, undergoing decompressive spinal surgery due to degenerative Lumbar Spinal Canal Stenosis (LSCS) in 2015 were included. Patients were divided in groups as per presence of RNR and assessed for spinal morphometric parameters. Results: Fifty-two patients, aged 57.52 ± 12.08 years, were enrolled in the study. The patients in RNR group were older than those in non-RNR group (p = 0.023). RNR was significantly associated with sedimentation sign (15 vs 11; p = 0.011), as well as L2/L3 (12 vs 9; p = 0.043) and L3/L4 (18 vs 18; p = 0.034) stenosis. Ligamentum flavum hypertrophy at the most stenotic level was more common in the RNR group (20 vs 19; p = 0.006). The only quantitative parameter statistically associated with RNR was lower ligamentous interfacet distance (5.07 ± 1.95 vs 8.07 ± 4.26 mm; p = 0.010). All other parameters did not contribute to the development of RNR in LSCS patients. The multivariate model revealed significant contribution of age, male sex, ligamentous interfacet distance and disc bulge to develop RNR. Conclusion: Certain spinal morphometric parameters contribute towards RNR formation, which represents higher degree of spinal stenosis. These parameters, along with RNR, should be regularly reported for preoperative consideration of LSCS management.